Business productivity and union ethics: a look at Colombia - Rincón Rodríguez, Isabel Cristina; Chaparro Medina, Jorge E.; Garazón Posada, Marcela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This text is born from the research project in business management that is being carried out in the business administration program where the authors are linked. The pursuit of business success and union ethics are presented as the purpose of consolidating Latin American sustainable development. In this sense, the new labor realities have recently been focusing on productivity, on the elimination of static work giving rise to remote work and the formation of synergistic work teams, which respond to the inclinations of this new offspring of subordinates, thus affecting to the trade union organizations that depend on the labor cloister.